A Bibliometric Analysis Of Psychological Measurement In Sports: Mapping Global Trends, Collaborations, Thematic Developments - Noor Akhmad (Gudang Jurnal Multidisiplin Ilmu, 2025)
Psychological measurement tools are fundamental in sports psychology for assessing mental toughness, performance anxiety, motivation, and resilience in athletes. Despite increasing research in this field, a comprehensive bibliometric analysis of global trends, collaboration networks, and thematic developments remains limited. This study conducts a bibliometric analysis of 489 Scopus-indexed articles published between 1977 and 2025 to examine publication trends, key contributors, and thematic structures. Results indicate that the United States (32.5%), United Kingdom (15.8%), Germany (9.6%), and Canada (7.3%) are the leading contributors, with emerging research from Slovenia (2.1%) and Uruguay (1.7%). Institutional collaborations highlight strong interdisciplinary ties, particularly between the Center for Addictive Disorders and the Faculty of Medicine and Health. Co-authorship analysis identifies Nikos Ntoumanis (98 publications) and Jennifer Cumming (76 publications) as pivotal researchers, while citation network analysis highlights influential clusters led by Joan L. Duda (4,532 citations) and Andreas Ivarsson (3,215 citations). Bradford’s Law identifies Psychology of Sport and Exercise and Journal of Applied Sport Psychology as core journals. Thematic mapping reveals that mental toughness (18.4%) and resilience (14.7%) are dominant topics, while psychometrics (6.3%) and competitive anxiety (5.1%) remain underexplored. These findings provide strategic insights for enhancing global research collaboration, bridging psychological theory and practice, and guiding future research directions in sports psychology.